Respiratory Management of Myotonic Dystrophy - John R Bach; Giulio Chiarello; Somnath Gonapa (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2020)
Patients with myotonic dystrophy can avoid episodes of respiratory failure by using up to continuous noninvasive ventilatory support (CNVS). Of 154 patients consecutively presenting to a neuromuscular disease clinic, 143 had types 1 or 2 and 11 had congenital myotonic dystrophy. Of the 76 who came multiple times, 41 were prescribed and used at least sleep NVS to relieve symptoms of fatigue and hypersomnolence. They had sleep and end-tidal (Pet) CO2 with highs over 50 mm Hg and many 4% or greater O2 desats per hour of sleep and all had mean sleep O2 sat levels less than 95% before beginning sleep NVS. Thirteen eventually had to extend NVS use into and eventually throughout daytime hours for CNVS. While using NVS during the day their arterial blood gases were within normal limits. When the 41 were using NVS only during sleep, 24 of the 41 also had normalization of diurnal SpO2 to ≥ 95% and decreased hypercapnia. The 41 patients have been using sleep NVS for 6.70±3.64 (range = 0.75 to 19) years per patient or for 274.7 patient-years. Seventy-two have died or been lost to follow-up. The 13 up to CNVS users have been doing so for 75.7 patient-years or a mean of 5.8±3.2 (range = 0.2 to 10) years per patient. The VC from first visit to most recent visit of all 71 decreased a mean 49.3±168.8 ml or about 1.5% per year. it decreased a mean 52±171 per year for the 41 NVS users over 274.7± 3.64 patient-years.